1990
DOI: 10.1121/1.399986
|View full text |Cite
|
Sign up to set email alerts
|

Coding of spectral fine structure in the auditory nerve. II: Level-dependent nonlinear responses

Abstract: Phase-locked discharge patterns of single cat auditory-nerve fibers were analyzed in response to complex tones centered at fiber characteristic frequency (CF). Signals were octave-bandwidth harmonic complexes defined by a center frequency F and an intercomponent spacing factor N, such that F/N was the fundamental frequency. Parameters that were manipulated included the phase spectrum, the number of components, and the intensity of the center component. Analyses employed Fourier transforms of period histograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Duifhuis (1970) and Wightman (1973) observed that, when listeners are presented with harmonic complexes from which specific harmonics have been removed, missing harmonics could potentially be derived from the temporal waveform. Horst, Javel, and Farley (1990) found that, when a center component of a harmonic complex was left out, this missing component was restored in the pattern of discharges in AN at higher stimulus levels. In recent studies of basilarmembrane mechanics, Rhode and Recio (2001) presented equal-interval seven-tone complexes.…”
Section: Additional Conditionsmentioning
confidence: 95%
“…Duifhuis (1970) and Wightman (1973) observed that, when listeners are presented with harmonic complexes from which specific harmonics have been removed, missing harmonics could potentially be derived from the temporal waveform. Horst, Javel, and Farley (1990) found that, when a center component of a harmonic complex was left out, this missing component was restored in the pattern of discharges in AN at higher stimulus levels. In recent studies of basilarmembrane mechanics, Rhode and Recio (2001) presented equal-interval seven-tone complexes.…”
Section: Additional Conditionsmentioning
confidence: 95%
“…Multi-harmonic stimuli are unique in that their waveforms have a distinct stable periodicity which corresponds exactly to the fundamental frequency of their harmonic series. A number of studies in the mammalian peripheral auditory system have shown that VIIIth nerve fibers can synchronize with high precision to the fundamental period of such multi-harmonic stimuli (Delgutte and Kiang 1984;Miller and Sachs 1984;Horst et al 1986;Deng et al 1987;Horst et al 1990;Palmer 1990).…”
Section: Synchronization Coding Of Phase Spectramentioning
confidence: 99%
“…And so, the obvious question arises as to whether an auditory fiber's synchronization to the fundamental period is sensitive to those changes, and thus, constitutes a mechanism of encoding phase information in a complex, periodic signal. The effects of phase shifts within multi-harmonic stimuli on the synchronization characteristics of auditory nerve fibers have been examined in several previous studies in cats (Horst et al 1986;Deng et al 1987;Horst et al 1990) as well as more recently in frogs (Simmons et al 1993). In cats, it was found that auditory nerve fibers exhibited a strong degree of synchronization to the fundamental period for stimuli which had "inphase" spectra, (i.e., stimuli in which the relative phase angles of all of the components were the same).…”
Section: Synchronization Coding Of Phase Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Horst et al (1986Horst et al ( , 1990 used multicomponent stimuli to analyze the representation of complex stimuli in responses of the auditory nerve in cat. In their study, the response to the center component became increasingly suppressed as the number of stimulus components increased (from 4 to 64).…”
Section: Introductionmentioning
confidence: 99%